2019
DOI: 10.3390/microorganisms7100405
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of The Retinal Pigment Epithelial Changes That Characterize The Ocular Lesion in Toxoplasmosis

Abstract: When a person becomes infected with Toxoplasma gondii, ocular toxoplasmosis is the most common clinical presentation. The medical literature describes retinitis with surrounding hyperpigmentation secondary to proliferative changes in the retinal pigment epithelium, which is sufficiently characteristic that investigation often is not needed to make the diagnosis. We aimed to establish the frequency of “typical” ocular toxoplasmosis and delineate its molecular basis. Among 263 patients presenting consecutively w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several molecules, such as VEGF, TGF-β, and angiopoietin, are known to be the key regulators of blood vessel development (Apte et al, 2019;Wang et al, 2019). VEGF is constitutively expressed in RPE to maintain physiological functions of the choroid and the RPE, however overexpression of VEGF can cause vascular disease in the retina of the eye and other parts of the body such as retinal edema, choroidal neovascularization and retinopathy of prematurity (Smith et al, 2004;Wiertz et al, 2010;dela-Torre et al, 2014;Lie et al, 2019;Mushtaq et al, 2019). The secretion of VEGF from RPE cells is induced by physical and chemical factors such as hypoxia, advanced glycation end products (AGEs), hyperthermia, epithelial membrane protein 2 (Emp2) and cytokines (Treins et al, 2001;Faby et al, 2014;Apte et al, 2019;Wang et al, 2019;Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several molecules, such as VEGF, TGF-β, and angiopoietin, are known to be the key regulators of blood vessel development (Apte et al, 2019;Wang et al, 2019). VEGF is constitutively expressed in RPE to maintain physiological functions of the choroid and the RPE, however overexpression of VEGF can cause vascular disease in the retina of the eye and other parts of the body such as retinal edema, choroidal neovascularization and retinopathy of prematurity (Smith et al, 2004;Wiertz et al, 2010;dela-Torre et al, 2014;Lie et al, 2019;Mushtaq et al, 2019). The secretion of VEGF from RPE cells is induced by physical and chemical factors such as hypoxia, advanced glycation end products (AGEs), hyperthermia, epithelial membrane protein 2 (Emp2) and cytokines (Treins et al, 2001;Faby et al, 2014;Apte et al, 2019;Wang et al, 2019;Sun et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasmic retinochoroiditis is one of the late consequences of ocular toxoplasmosis, and choroidal neovascularization is a severe complication of ocular toxoplasmic retinochoroiditis (Commodaro et al, 2009;Pleyer et al, 2014). There is ample evidence that VEGF secretion by RPE cells leads to neovascularization in the eye (Rezzola et al, 2014;Lie et al, 2019;Mushtaq et al, 2019). Nevertheless, information regarding the mechanisms of angiogenesis in ocular toxoplasmosis is limited.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to multiple roles in retinal homeostasis, including maintenance of the bloodretinal barrier, the retinal pigment epithelium has been identified as a key host cell for a range of micro-organisms, including some bacteria and parasites (e.g., Mycobacteria tuberculosis and Toxoplasma gondii) [38,39], and a host of different viruses including flaviviruses (e.g., DENV, Zika virus [ZIKV], West Nile virus), herpesviruses (e.g., herpes simplex virus, varicella zoster virus, cytomegalovirus), and filoviruses (i.e., Zaire ebolavirus) [40][41][42][43][44][45]. Ophthalmic imaging studies in patients have documented changes implicating the retinal pigment epithelium in other infectious diseases (e.g., syphilis and coronavirus disease 2019) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Retinal hyperpigmentation is a very characteristic change during OT, mostly due to cell proliferation forming a multilaminar layering of the RPE. A recent study showed that this cell proliferation is due to an increase of Vascular Endothelial Growth Factor A (VEGF-A) and Insulin-like Growth Factor 1 (IGF-1), along with a decrease in Thrombospondin 1 (TSP1) in infected cells [41,42]. Both VEGF-A and IGF-1 are proangiogenic proteins, while TSP1 is antiangiogenic [43,44].…”
Section: Infection Of the Rpe By T Gondiimentioning
confidence: 99%